Overlay Journals: Overlooked or Emergent? - Thornton, Gail; Kroeker, Emily (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2021)
Overlay journals are not a new concept but have been experiencing a recent resurgence because of the increase in the number of preprint servers and the increase in the number of preprints on coronavirus disease 2019 (COVID-19) related topics. This study examines overlay journals at various stages of maturity for unique characteristics, including whether the authors submitted their article to the journal and whether the reviews of the article are published by the overlay journal. Whether they are considered overlooked or emergent, overlay journals are becoming an important contribution to scholarly communication.